Isolated Intracardiac Metastasis: The First Sign of Hepatocellular Carcinoma - Anusca Paixão (Karger Publishers, 2021)
Metastatic hepatocellular carcinoma (HCC) to the right atrium without invasion of the inferior vena cava is a very rare and difficult diagnosis, especially when the primary tumour is yet to be known. A 68-year-old man with symptoms of heart failure was admitted to the emergency department; his transthoracic echocardiogram showed a mass comprehending almost the totality of the right atrium, obliterating its entrance nearly completely and impeding the normal auricular–ventricular flux, described as a possible auricular myxoma. The patient was promptly transferred to cardiothoracic surgery and submitted to an urgent surgery to completely remove the mass, which was macroscopically described as suspected of malignancy. Further investigation demonstrated a single nodule in the liver with malignant imaging characteristics, and the histology confirmed the diagnosis of metastatic HCC of the right atrium, without metastatic disease elsewhere. He was then submitted to radiofrequency ablation and medicated with sorafenib. The disease progressed slowly but subsequently involved the inferior vena cava and portal vein, culminating in his death 4 years and 3 months after the diagnosis. Although the prognosis for metastatic HCC may be poor, especially with intracavitary heart metastasis, this case shows that an aggressive initial approach with surgical metastasectomy may prolong the median survival of the patients.